Circadian gene × environment perturbations influence alcohol drinking in Cryptochrome‐deficient mice. (20th October 2021) - Hühne, Anisja; Echtler, Lisa; Kling, Charlotte; Stephan, Marius; Schmidt, Mathias V.; Rossner, Moritz J.; Landgraf, Dominic
Abstract: Alcohol use disorder (AUD) is a widespread addiction disorder with severe consequences for health. AUD patients often suffer from sleep disturbances and irregular daily patterns. Conversely, disruptions of circadian rhythms are considered a risk factor for AUD and alcohol relapses. In this study, we investigated the extent to which circadian genetic and environmental disruptions and their interaction alter alcohol drinking behaviour in mice. As a model of genetic circadian disruption, we used Cryptochrome1/2 ‐deficient ( Cry1/2 −/− ) mice with strongly suppressed circadian rhythms and found that they exhibit significantly reduced preference for alcohol but increased incentive motivation to obtain it. Similarly, we found that low circadian SCN amplitude correlates with reduced alcohol preference in WT mice. Moreover, we show that the low alcohol preference of Cry1/2 −/− mice concurs with high corticosterone and low levels of the orexin precursor prepro‐orexin and that WT and Cry1/2 −/− mice respond differently to alcohol withdrawal. As a model of environmentally induced disruption of circadian rhythms, we exposed mice to a "shift work" light/dark regimen, which also leads to a reduction in their alcohol preference. Interestingly, this effect is even more pronounced when genetic and environmental circadian perturbations interact in Cry1/2 −/− mice under "shift work" conditions. In conclusion, our study demonstrates that in mice, disturbances in circadian rhythms have pronounced effects on alcohol consumption as well as on physiological factors and other behaviours associated with AUD and that the interaction between circadian genetic and environmental disturbances further alters alcohol consumption behaviour. Abstract : In this study, we investigated the impact of endogenous and environmental circadian disturbances, and their interaction, on alcohol consumption in mice. We found significant changes in response to both forms of disturbances which were even more pronounced when they co‐occurred. We provide underlying molecular mechanisms that contribute to the understanding of the observed behavioural phenotypes of the mice.